2022
DOI: 10.5194/acp-22-7739-2022
|View full text |Cite
|
Sign up to set email alerts
|

Highly time-resolved chemical speciation and source apportionment of organic aerosol components in Delhi, India, using extractive electrospray ionization mass spectrometry

Abstract: Abstract. In recent years, the Indian capital city of Delhi has been impacted by very high levels of air pollution, especially during winter. Comprehensive knowledge of the composition and sources of the organic aerosol (OA), which constitutes a substantial fraction of total particulate mass (PM) in Delhi, is central to formulating effective public health policies. Previous source apportionment studies in Delhi identified key sources of primary OA (POA) and showed that secondary OA (SOA) played a major role bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…Relative humidity ranged from 30% to 100%. More detail on the campaign site itself and the aerosol and gas-phase instrumentation can be found in other publications from this campaign (Lalchandani et al, 2021;Rai et al, 2020;Singh et al, 2021b;Wang et al, 2020;Kumar et al, 2022).…”
Section: Field Campaign and Sampling Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Relative humidity ranged from 30% to 100%. More detail on the campaign site itself and the aerosol and gas-phase instrumentation can be found in other publications from this campaign (Lalchandani et al, 2021;Rai et al, 2020;Singh et al, 2021b;Wang et al, 2020;Kumar et al, 2022).…”
Section: Field Campaign and Sampling Sitementioning
confidence: 99%
“…CC BY 4.0 License. inlet for gases and aerosols (FIGAERO-CIMS) in January and February 2019, as part of a larger-scale effort to characterise physical and chemical properties of Delhi's urban haze (Lalchandani et al, 2021;Rai et al, 2020;Singh et al, 2021a;Kumar et al, 2022). During the campaign, we observed particulate chloride loadings in excess of 100 µg m -3 on several occasions.…”
Section: Introductionmentioning
confidence: 99%
“…AMS is commonly limited to short time periods due to the high maintenance of the AMS measurements and their high operating costs. As a result, only a few studies run AMS continuously (e.g., see Kumar et al, 2022 andO'Dowd et al, 2014). However, there was still a strong need for such a long-term analysis.…”
Section: Introductionmentioning
confidence: 99%
“…From all ASCM/AMS stations (22 stations;Chen et al, 2022) only Melpitz as a rural-background site and Krakow as an urbanbackground site showed the coal combustion emissions with the maximum contribution during winter for both sites (Krakow: 18.2 % and Melpitz: 23 %) compared to summer (Krakow: 4.5 % and Melpitz: 8.7%). The drastic seasonal changes in Krakow are attributed to the common use of coal burning for residential heating reasons during the winter time(Casotto et al, 2022;Tobler et al, 2021), while in Melpitz, as discussed above, coal combustion is affected by both surrounding and transported emissions from other sites.…”
mentioning
confidence: 99%
“…Source apportionment studies in Zurich using an EESI-TOF identified SOA factors from monoterpene oxidation in summer (Stefenelli et al, 2019) and oxidation of biomass-burning emissions in winter (Qi et al, 2019). EESI-TOF measurements identified SOA factors related to solid fuel combustion and aqueous-phase processes in Beijing (Tong et al, 2021) and SOA factors with aromatic and biogenic origins in Delhi (Kumar et al, 2022). However, to date, the factor concentrations returned by PMF analyses using these instruments are not quantitative.…”
Section: Introductionmentioning
confidence: 99%